Detergent-resistant plasma membrane proteome to elucidate microdomain functions in plant cells - Takahashi, Daisuke; Kawamura, Yukio; Uemura, Matsuo (Frontiers in Plant Science, 2013)
Although proteins and lipids have been assumed to be distributed homogeneously in the plasma membrane (PM), recent studies suggest that the PM is non-uniform, forming a structure that includes a number of lateral domains enriched in specific components, such as sterols, sphingolipids, and integral and surface-bound proteins. These domains are called microdomains and are considered the platform for biochemical reaction centers involved in various physiological processes. Microdomains can be extracted as detergent-resistant membrane (DRM) fractions, and such fractions have been isolated from some plant species and used for proteomic and other biochemical characterizations to gain understanding of microdomain functions. Profiling sterol-dependent proteins using a putative microdomain-disrupting agent suggests specific lipid-protein interactions in microdomains. Furthermore, in some plant species, DRM proteomes dynamically respond to biotic and abiotic stresses. Taken together, these results suggest that DRM proteomic studies provide important information for understanding microdomain physiological functions that are critical to the successful prosecution of a plant’s life cycle, particularly in its development and stress responses.